Use of Interactive Learning Media to Improve Student Learning Outcomes in Pneumatic Subject Matter Electronic Control System - Agus Hariyanto; Rufii Rufii (Jurnal Penelitian Pendidikan, 2024)
Learning Media is a learning tool used by someone using tools created to make it easier to deliver material when teaching at school. Based on observations made by the teacher, the findings were: (a) there were 12 students out of a total of 29 who had not yet reached the KKM; Students' interest in learning is lacking, students look less enthusiastic when the teacher explains the material presented. Based on the description above, the author wishes to examine this problem, through research with the title "Use of Interactive Learning Media to Improve Student Learning Outcomes in Pneumatic Materials in Electronic Control Systems Subjects in Class XII 1 TEI SMKN 1 Jetis". This type of research is classroom action research (PTK). The learning media used is Adobe Flash software. This research was conducted in three cycles, the subjects of this research were 29 class XII TEI 1 students. Data collection techniques are through observation sheets, questionnaires and formative tests. Analysis of the interest in learning questionnaire shows that the average student interest in learning has increased from 2.5 with the criterion of less interest to 3.2 with the criterion of interest while the average score obtained at Student learning outcomes increased in cycle I by 71.38, cycle II by 75.86 and cycle III by 83.10. Based on these results, it can be concluded that the use of interactive learning media has a positive impact in increasing students' interest in learning and can improve the learning outcomes of class XII TEI 1 SMK Negeri 1 Jetis students.